Penggunaan Metode Mind Mapping sebagai Upaya untuk Meningkatkan Kompetensi Writing teks descriptive - Fauziatul Halim (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Langsa, 2019)
In MTs Negeri Langsa many students of class VII who find it difficult to write monologue text in the form of descriptive. This is due to the lack of memorized vocabulary and its meaning and lack of grammar or grammar mastery. This happens because most students are less interested in English subjects. After all, they consider English as a difficult and uninteresting subject. The purpose of this study to find out the use of the Mind Mapping method can improve the ability of Grade VII.1 MTsN students in writing texts. descriptive. The methodology used is class action research (CAR). The research subject was class VII I MTsN Langsa. The observations during the study showed that students seemed enthusiastic as soon as the mind mapping method was introduced until it was applied to writing. When working on assignments, everyone can collect tasks. From the results of processing the data, the percentage of mastery learning in Cycle I was 39%, in Cycle II it was 100%. These results indicate an increase in each cycle. Based on the results of the study, the researcher suggested that English Language MTs teachers use the mind mapping method for learning aspects of writing and other aspects of learning. In addition to being able to grow creativity and attractiveness, this method also contains various methods and can generate ideas.